Chromosomes of Pseudapanteles dignus (Muesebeck, 1938) and a review of known karyotypes of the subfamily Microgastrinae (Hymenoptera, Braconidae) - Gokhman, Vladimir E. (2024)
The karyotype of Pseudapanteles dignus (Muesebeck, 1938), an important parasitoid of a serious tomato pest Phthorimaea (= Tuta) absoluta Meyrick, 1917 (Lepidoptera, Gelechiidae), in the Neotropics and adjacent regions, was studied for the first time using morphometric analysis and several techniques of differential chromosome staining, i.e., C-banding and staining with base-specific fluorochromes, together with fluorescence in situ hybridization (FISH) with an 18S rDNA probe. We found n = 7 and 2n = 14 in P. dignus, with seven metacentric chromosomes of similar size in the haploid set. C-banding revealed various C-positive bands, either centromeric or interstitial, on most chromosomes. Both AT-specific and GC-specific fluorochromes, 4’6-diamidino-2-phenylindole (DAPI) and chromomycin A3 (CMA3) respectively, showed uniform staining of chromosomes. FISH visualized a single subterminal rDNA site on a medium-sized metacentric. A brief review of known chromosome sets of the subfamily Microgastrinae (Braconidae) is given; certain features of karyotype evolution of this group are discussed.